Fractal analysis and histomolecular phenotyping provides insights into extracellular matrix remodeling in the developing bovine fetal ovary - Franchi, Fernanda Fagali [UNESP]; Hernandes, Mariana Pelicho; Coalho Ferreira, Amanda Leticia; Vieira de Lima, Victor Augusto; de Oliveira Mendes, Leonardo; Musa de Aquino, Ariana [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; César de Souza Castilho, Anthony (Elsevier, 2020)
Although studies have focused on extracellular matrix (ECM) remodeling during the formation and functioning of adult ovaries, there is no comprehensive understanding of the mechanisms controlling preantral follicle development in fetal bovine ovaries during gestation. Thus, to gain insights into ECM remodeling during initial ovarian development, we used fetal ovaries to quantify the fractal dimension (FD), total collagen, and relative mRNA abundance of genes related to ECM remodeling (COL1A1, COL1A2, COL4A1, MMP2, MMP9, MMP14, TIMP1, and TIMP2). For this, pairs of fetal ovaries were obtained from cows in a local abattoir at days 60, 90, 120, and 150 of gestation; one of each pair was submitted to RNA extraction for target transcript analysis, and the other was used for total collagen and FD evaluation. From day 120 total collagen appeared to occupy a greater area in the fetal ovary. The fractal analysis with picrosirius red staining shows higher at day 150 when compared with that on day 60. On the contrary, we found an inverse pattern when we used the hematoxylin and eosin staining approach. Concerning target gene expression, the relative abundances of COL1A1, COL4A1, MMP2, MMP14, TIMP1, and TIMP2 mRNA were higher on day 150 when compared with that on day 60. We conclude that fractal analysis reflects the morphological changes occurring during structural organization of the fetal ovary and that the expression of genes related to ECM remodeling is modulated throughout gestation in bovine fetal ovaries.
Keywords: Cattle; Collagen; Gene expression; Metalloproteinases; Picrosirius; Preantral follicles